Reflections on the Nature of an Energy Company: Inspirations from Stanisław Kasznica (Contemporary Central & East European Law, 2024)
In his manual Polish Administrative Law Stanisław Kasznica dedicates a section to public institutions, which can be categorised into public establishments (e.g. public schools) and public undertakings (e.g. state-owned banks) based on their purpose and the governing law. The author explores how Kasznica’s insights can aid in understanding the nature of a public undertaking, as regulated by contemporary law and discussed in case law and doctrine. He concludes that it is worth considering whether the legal definition of an energy company should reflect its fundamental role in the economy and society, given the universal good it provides in the market. Furthermore, he suggests that defining public undertakings legally would be valuable.